Student olympiad in psychology «PsyOlymp»: design and implementation experience - Saladukha, Aliaksandr S.; Fofanova, Galina A.; Smirnova, Yuliya S. (University Pedagogical Journal, 2023)
The article discusses the methodology for organising the student olympiad in psychology «PsyOlymp». The general methodological principles underlying the olympiad are outlined – the principles of openness, gamification, historicism, scientificity, heuristics. A description of the general logic of the conduct and content structure of the first and second stages of the olympiad is provided. The psychological characteristics of the tasks implemented with the help of olympiad tasks are given.